Seismic Performance of X-Braced Frame with Vertical Link Beam (XBF-VLB) - Nouri, Pouria (International Journal of Sustainable Construction Engineering and Technology, 2023)
X-braced Frames(XBFs), one of the most prevalent lateral load-resisting structures, has low energy dissipation and ductility. This study investigates the behavior of a single-story, single-span X-braced frame equipped with a Vertical Link Beam (XBF-VLB) under monotonic and cyclic loading using the nonlinear finite element technique in the Abaqus software and validated with experimental data. The VLBs were positioned where the bracing members were connected to the beam in double, single, and wide forms. The impacts of the length, depth, and the number of links, stiffeners, and other VLB section parameters were assessed. The A36 steel ductile damage method (DDM) estimated the damage of the main structural members, such as bracing members. The results revealed that X-braced frames with single, double, and wide form Vertical Link Beams (XBF-VLBs) performed better under cyclic and monotonic loading than X-braced frames without Vertical Link Beam (XBFs). Likewise, because the bracing members did not buckle in the XBF-VLB specimens, there was no rapid loss in the stiffness and strength of the X-braced frames. Also, the results of the cyclic loading of the XBF-VLB specimens demonstrated that no rapid drop in stiffness or strength was detected due to no buckling of the bracing members under the cyclic loading, as was the case with the monotonic loading. Additionally, compared to the XBF specimens, the drifts corresponding to the first plastic hinges of the XBF-VLB specimens show that the bracing members experienced nonlinear deformation at greater drifts, with the plastic hinges created in them at bigger displacements. According to the cyclic loading results, the VLB also reduced Von Mises stress and damage in the bracing members of the XBF-VLB specimens. Moreover, the ultimate von Mises stress reduction in the bracing members of the models with VLBs equals 33%, which prevents buckling.